Impacts of Geotechnical Issues on Design of the Beacon Hill Tunnel and Station Project - Robert A. Robinson; Michael S. Kucker; Michael J. Lehnen; Stuart Warren; David McAllister (Society for Mining, Metallurgy & Exploration, 2005)
Geotechnical conditions exposed by the phased exploration programs have had a major impact on the selection of excavation and support methods, dewatering requirements, size of openings, vertical alignment, and estimated cost of construction for the Beacon Hill Tunnel and Station section of the “Link” Light Rail. Beacon Hill is comprised of a very complex glacial geology, including numerous slickensided fractures, injected sand dikes, and multiple perched groundwater levels as revealed by a phased boring program and exposed in a test shaft. The Geotechnical Baseline Report (GBR) presents this complex geology along with a “tool box” of alternative additional support systems to accommodate the varying ground conditions during construction of the station excavation. Additional explorations will also be accomplished during construction to further refine the geotechnical interpretations and provide an opportunity to use pro-active ground improvement techniques to optimize the station excavation and support requirements.